Words and Things and "The Kuba Miracle". (4th June 2018) - Kriger, Colleen E.
Abstract: The essay revisits Vansina's work on the Kuba kingdom, drawing together art historical, historical linguistic, written documents, and oral sources. It argues that Vansina's eclectic methodology fostered continual revision to his historical conclusions as new material in one of those threads forced rethinking interpretations of the others. Vansina's captions to images of material forms from Kuba exemplify skilled compression while figuring African audiences, artisans, and owners of objects with humor and respect. Résumé: Cet article revient sur le travail de Jan Vansina portant sur le royaume de Kuba, en rassemblant des sources écrites, orales et issues de l'histoire de l'art. Il montre que la méthodologie éclectique de Vansina a favorisé la révision continuelle de ses conclusions historiques grâce à l'apport de nouvelles sources qui l'ont forcé à repenser ses interprétations. Les légendes d'images écrites par Vansina pour les objets de la culture matérielle de Kuba montrent à quel point il savait être concis et habile tout en représentant le public africain, les artisans et les propriétaires d'objets avec humour et respect.